Legal Review Of The Criminal Act Of Participating In Changing The Recapitulation Of Votes In The Election (Decision Study Number: 523/Pid.Sus/2019/Pn.Ckr) - Hariono Sianturi; Rahul Ardian Fikri; T. Riza Zarzani (International Journal of Society and Law, 2024)
General elections are a fundamental pillar of democracy, ensuring the sovereignty of the people through fair and honest electoral processes. The integrity of vote recapitulation is crucial for democratic elections, yet it remains susceptible to fraud and manipulation, undermining public trust and electoral legitimacy. This study examines the application of material criminal law and judicial considerations in Decision Number 523/Pid.Sus/2019/PN.Ckr, a case involving negligence resulting in alterations to vote recapitulation minutes. The research highlights the legal framework, including the sanctions under Law Number 7 of 2017, and explores the challenges in law enforcement due to the complexities of election crimes. Through analysis of the case, the study emphasizes the importance of accountability and consistent enforcement to safeguard electoral integrity and deter future violations.